The Superficial Femoral Artery Flap: A 3-Dimensional Anatomical Study. Issue 3 (August 2017) - El-Hadi, Hadal; Morris, Steven; Alkhawaji, Ali
Background: The superficial femoral artery perforator (SFAP) flap offers advantages for pedicled transfer including consistent perforators and vascular territory, well-hidden donor site scar, and hairless flap skin. This article provides a historical overview of the SFAP flap and describes the vascular anatomy of the SFAP by 3-dimensional analysis and angiography. Methods: Ten fresh cadavers were injected using the lead oxide technique through the femoral artery. Spiral computed tomographic scanning and 3-dimensional evaluation were used to describe the SFAP number, diameter, length, type, and location. Results: A total of 288 perforators in 15 cadaver limbs were identified; 19 ± 8 perforators per thigh ≥0.5 mm in diameter, with an average diameter of 0.8 ± 0.3 mm and a range of 0.5 to 2.1 mm; the mean length of each perforator was 68 ± 31 mm; 45% were septocutaneous and 55% were musculocutaneous. The medial thigh region was divided into 6 areas (anterior and posterior halves, then the proximal third, middle third, and distal third of each). The majority of the perforators were located in the middle and distal thirds of the anteromedial thigh (33% each). Conclusions: Using 3-dimensional vascular anatomical analysis, the number, location, length, type, and diameter of the SFAP were documented. In the literature, relatively few reports of the use of the SFAP flap are available, however, this is a valid donor site with consistent cutaneous perforators suitable for harvest as a local or regional flap transfer. This is the first 3-dimensional vascular anatomical study to comprehensively document the vascular anatomy of the SFAP flap.